2002
DOI: 10.2527/2002.8051250x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in performance, blood parameters, humoral and cellular immune responses in weanling piglets exposed to low doses of aflatoxin1

Abstract: A feeding trial was conducted to evaluate the effect of aflatoxin (AF)-contaminated diets on growth and hematological and immunological parameters. Low doses of aflatoxins (140 and 280 ppb) were included in a corn-soybean diet provided for ad libitum consumption to 36 weanling piglets for a period of 4 wk. A "dose-related" decrease in weight gain was observed in treated animals. This effect was significant (P < 0.05) in the 280 ppb-treated group compared to the control group. Ingestion of AF-contaminated feed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
97
5
11

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(124 citation statements)
references
References 22 publications
11
97
5
11
Order By: Relevance
“…Previous studies have shown that AFB 1 has a range of negative effects on poultry health, including poor performance (Oguz and Kurtoglu, 2000;Magnoli et al, 2011), liver and kidney lesions (Ortatatli et al, 2005), immunity damage (Marin et al, 2002), and hematology problems (Zhao et al, 2010). Moreover, the tissue deposition and residue of AFB 1 in poultry has also been determined (Oliveira et al, 2000(Oliveira et al, , 2003.…”
mentioning
confidence: 99%
“…Previous studies have shown that AFB 1 has a range of negative effects on poultry health, including poor performance (Oguz and Kurtoglu, 2000;Magnoli et al, 2011), liver and kidney lesions (Ortatatli et al, 2005), immunity damage (Marin et al, 2002), and hematology problems (Zhao et al, 2010). Moreover, the tissue deposition and residue of AFB 1 in poultry has also been determined (Oliveira et al, 2000(Oliveira et al, , 2003.…”
mentioning
confidence: 99%
“…This is the first report of AF intoxication of piglets through the milk of sows, which is the primary nutriment of piglets of this age. Many other authors have reported the adverse effect of AF in pigs, and this effect is primarily reflected in the reduction of the production performance (average daily gain, feed conversion ratio and morbidity) and immunosuppressive effect depending on the ingested quantity of AF and the age of the individual piglets [8][9][10][11] . Their studies were conducted on older piglets exhibiting chronic effects [12,13] , while in suckling piglets, much lower AF quantities can produce a lethal effect, as in our current report.…”
Section: Discussionmentioning
confidence: 99%
“…Oral doses of AF decreased the number of lymphoid cells and reduced peritoneal macrophage phagocytosis in weanling rats (Raisuddin et al, 1990), reduced lymphocyte 12 SABOURIN ET AL. blastogenesis and antibody response in mice (Reddy et al, 1987), impaired alveolar macrophage phagocytosis in rabbits (Richard and Thurston, 1975), and reduced complement activity in guinea pigs (Thurston et al, 1972(Thurston et al, , 1974. Low dose AF reduced the humoral immune response induced by Mycoplasma agalactiae (Marin et al, 2002).…”
Section: Introductionmentioning
confidence: 94%
“…AF ingestion does not appear to alter immunoregulatory cytokine production (Dugyala and Sharma, 1996;Watzl et al, 1999;Marin et al, 2002) or the humoral response to sheep red blood cells (van Heugten et al, 1994) and Erysipelothrix rhusiopathiae (Panangala et al, 1986). Weanling pigs fed low doses of AF for 4 weeks, displayed no alterations in the relative numbers of blood cells, globulin, albumins, serum protein concentration, or phytohemagglutinin (PHA)-induced expression of IL-2 or IL-4 using whole blood, indicating that there was no effect of AF on the cell-mediated immune response (Marin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation